Effects of solvent extraction and drying methods of Malaysian seaweed, Sargassum polycystum on Fucoxanthin content - Shukor, Muhammad Idham; Darnis, Deny Susanti; Sabarudin, Nur Syazwani; Mohammad Noor, Normawaty; Bakhtiar, Muhammad Taher (2021)
This study aims to evaluate the effects of solvents extraction and drying methods on selected fucoxanthin content in Sargassum polycystum that was collected from Blue Lagoon, Port Dickson Malaysia. Two different drying methods were used in this study, i.e sun-drying and air-drying. Acetone, methanol and ethanol were used solvents to extract the fucoxanthin from S. polycystum. The results showed that both drying methods and solvents extraction had a statistically significant effect (p < 0.05) on fucoxanthin content in S. polycystum. Among three solvents extraction with two drying methods investigated, acetone extract from air-dried sample gave the highest fucoxanthin content (0.282 ± 0.08 mg/g DW) followed by ethanolic extract from air-dried sample (0.198 ± 0.13 mg/g DW). Sun-drying sample extracted with methanol yielded the lowest amount of fucoxanthin (0.028 ± 0.02 mg/g DW). Concisely, the best drying method to extract fucoxanthin from S. polycystum is air-drying method with acetone as the solvent extract.